Analysis of risk communication teaching in psychosocial and other medical departments - Baessler, Franziska; Zafar, Ali; Ciprianidis, Anja; Wagner, Fabienne L.; Klein, Sonja Bettina; Schweizer-Schubert, Sophie; Bartolovic, Marina; Roesch-Ely, Daniela; Ditzen, Beate; Nikendei, Christoph; Schultz, Jobst-Hendrik (Medical education online, 2020)
Aims: Teaching students about risk communication is an important aspect at medical schools given the growing importance of informed consent in healthcare. This observational study analyzes the quality of teaching content on risk communication and biostatistics at a medical school.Methods: Based on the concept of curriculum mapping, purpose-designed questionnaires were used via participant observers to record the frequency, characteristics and context of risk communication employed by lecturers during teaching sessions for one semester. The data was analyzed quantitatively and descriptively.Results: Teaching about risk communication was observed in 24.4% (n = 95 of 390) sessions. Prevalence varied significantly among different departments with dermatology having the highest rate (67.9%) but lesser in-depth teaching than medical psychology where risk communication concepts were discussed on a higher scale in 61.4% sessions. Relevant statistical values were not mentioned at all in 69% of these 95 sessions and clinical contexts were used rarely (55.8%). Supplementary teaching material was provided in 50.5% sessions while students asked questions in 18.9% sessions.Conclusions: Students are infrequently taught about communicating risks. When they are, the teaching does not include the mention of core biostatistics values nor does the teaching involve methods for demonstrating risk communication.